Dampak Perkembangan Teknologi Informasi dan Komunikasi terhadap Perilaku Intoleransi dan Antisosial di Indonesia - Rafles Abdi Kusuma (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The paper aims to exploration how the impact of the information and technology development in Indonesia. Especially, focus on the raising of the attitude and behavior that tend toward intolerant and antisocial. That behavior and attitude extremely were disturbing our social life. The flood of information in cyberspace causes disinformation that makes people split into poles of homogeneity, so people are not accustomed to a difference and are not trained to see problems from various sides. The transformation process taking place with a multilayer communication model has resulted in humans who are more individualistic and communalism, which leads to intolerant and antisocial behavior. Even today, communities are still divided into groups called